Erythroxylum calyptratum (Erythroxylaceae), a new species from Mt. Fansipan, northern Vietnam - Komada, Natsuki; Tagane, Shuichiro; Ngoc, Nguyen Van; Binh, Hoang Thi; Son, Hoang Thanh; Toyama, Hironori; Nagamasu, Hidetoshi; Naiki, Akiyo; Yahara, Tetsukazu (Phytotaxa, 2018)
Erythroxylum calyptratum, sp. nov. (Erythroxylaceae), from Mt. Fansipan, Hoang Lien National Park, Lao Cai Province, northern Vietnam, is newly described. The new species is characterized by thinly chartaceous leaves with 2–3 mm long petiole, 1–3 flowered inflorescences, downward facing white flowers, well-developed petal appendages (1/3–1/2 length of petals) and entirely free 3 styles. A description, illustrations, DNA barcodes of rbcL and matK and a key to the species of Erythroxylum in Indochina are provided.